2014
DOI: 10.1088/1612-2011/11/3/035602
|View full text |Cite
|
Sign up to set email alerts
|

In vivoenhancement of imaging depth for optical coherence tomography by eudermic agents on ridged and meshed human skin

Abstract: Non-invasive skin analysis by optical coherence tomography (OCT) is limited because of the absorption and scattering properties of the tissue. There are several possibilities for enhancing OCT images. The purpose of this study was to demonstrate that image quality can be improved using the hyperosmolar agents glucose and glycerol while investigating human ridged and meshed skin areas, without causing damage to the tissue. The experiments were carried out on the palm and the forearm of ten volunteers. After app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The minimum amount of scattering for collaborative effects should be further studied. The ultimate goal of deep-tissue imaging is to achieve penetration depth enhancement in vivo 23,57,58 . We anticipate that in vivo application can be realized in the near future because OCA and WS-OCT have worked successfully in in vivo environments.…”
Section: Resultsmentioning
confidence: 99%
“…The minimum amount of scattering for collaborative effects should be further studied. The ultimate goal of deep-tissue imaging is to achieve penetration depth enhancement in vivo 23,57,58 . We anticipate that in vivo application can be realized in the near future because OCA and WS-OCT have worked successfully in in vivo environments.…”
Section: Resultsmentioning
confidence: 99%
“…For example, when human palm skin was treated with glucose in vivo, the improvement in imaging depth of OCT reached a peak after 15 min and then gradually declined, which indicated that about 15 min after optical clearing was the optimal time to perform imaging in this case. 12 chemical, and microbial threats, making it particularly susceptible to damage and a variety of associated diseases have not yet been fully understood. On the other hand, there is a close link between the effects of some diseases on the skin and internal organs, such that the skin might be implicated when other organs become diseased.…”
Section: In Vivo Skin Optical Clearing For Improvement Of Imaging Per...mentioning
confidence: 99%
“…In turn, the skin will react to these changes by rehydration, metabolism of agents, and so on, leading to a reduction in the optical clearing effect. For example, when human palm skin was treated with glucose in vivo , the improvement in imaging depth of OCT reached a peak after 15 min and then gradually declined, which indicated that about 15 min after optical clearing was the optimal time to perform imaging in this case 12 …”
Section: In Vivo Skin Optical Clearing For Improvement Of Imaging Per...mentioning
confidence: 99%
See 1 more Smart Citation
“…Optical coherence tomography (OCT) is one of the powerful bio-imaging modalities that allows non-invasive, in vivo analysis of a biological specimen with micrometer resolution over a millimeter depth range. Because of its capability to perform subsurface imaging with high resolution and sensitivity, OCT has gained increased attention among researchers and found wide applicability in the areas of biological research and medical practice [4,5]. Nowadays researchers are showing substantial interest in Fourier domain OCT systems over the traditional time domain version as they are proven to be more efficient in terms of sensitivity and imaging speed [6].…”
Section: Introductionmentioning
confidence: 99%